# One grain of sand approximately weighs 7 * 10^{-5} g. How many grains of sand are there in 6300 kg of sand? Give your answer in standard form.

Proportion states that the two ratio or fractions are equal.

Given the statement: One grain of sand approximately weighs 7 * 10^{-5} g.

To find how many grains of sand are there in 6300 kg of sand.

Let x be the number of grains of sand in 6300 kg of sand.

Using conversion :

1 kg = 1000 g

6300 kg = 6300000 g

Then, by using proportion method, we have;

By cross multiply we get;

or

[using ]

Divide both sides by 7 we get;

Standard form is a way of of writing down very large or very small numbers easily.

Therefore, grains of sand are there in 6300 kg of sand.

## Related Questions

2 rectangular prism have a combined volume of 432 cubic feet. Prism a has half the volume of prism b. what is the volume of prism a? prism b

Let the volume of prism A be X. Then the volume of prism B is 2X. The combined volume could be described like this:

432 = X + 2X

Solving the equation,
432 = 3X
432/3=X
144=X

The volume of A is 144 cubic feet, while the volume of  B is 288 cubic feet.

One number is 3 more than another. The difference between their square is 63. What are the numbers?

X = y + 3
x^2 - y^2 = 63

(y + 3)^2 - y^2 = 63
(y + 3)(y + 3) - y^2 = 63
y^2 + 6y + 9 - y^2 = 63
6y + 9 = 63
6y = 54
y = 54/6
y = 9

x = y + 3
x = 9 + 3
x = 12

check...
x^2 - y^2 = 63              x = y + 3
12^2 - 9^2 = 63           12 = 9 + 3
144 - 81 = 63               12 = 12 (correct)
63 = 63 (correct)

ur 2 numbers are 9 and 12

Which equation has no solution?
(-x-3)=5
(2x-1)=0
(5-3x)=-8
(-x+9)=0​

All the given equations have solutions.

Step-by-step explanation:

To find the solution for (-x-3)=5

(-x-3)=5

-x + 3 = 5

x - 3 = -5

x = -5 + 3 = -2

x = -2

To find the solution for (2x-1)=0

(2x - 1) = 0

2x - 1 = 0

2x = 1

x = 1/2

To find the solution for (5-3x)=-8

(5 - 3x) = -8

5 - 3x = -8

-3x = -8 -5

-3x = -13

x  = -13/-3

x = 13/3

To find the Solution for (-x+9)=0​

(-x + 9) = 0

-x + 9 = 0

x = 9

Complete the first step in writing the equation of a circle in graphing form. EQUATION: x^2 -2x+y^2+6y-6=0 STEP 1: x^2-2x+y^2+6y=[1]